Can you hear me? - Accessing the voice of the child with Autism and their parent - Twomey, Miriam (Educação, 2020)
The aim of this paper is to access the voices of children with Autism Spectrum Disorders and their parents. This paper engages with philosophical conceptual frameworks exploring concepts of movement and engagement in eliciting child and parent voice. Qualitative, longitudinal case studies were conducted. Semi-structured interviews [n=83] were conducted with stakeholders including parents. Children with and without the label of Autism engaged in interventions drawing on the Creative Arts. Living autoethnography was considered a methodological tenet, establishing connectivity between life and research, self and others, providing a window through which the internal world of the parent was interpreted and understood. This research enabled children and parents to explore their worlds and deliberate on areas that affected their lives. The potential value for using the Creative Arts as a means of engaging children with Autism is discussed. Implications relating to movement [literal and metaphoric] and engagement are explored. ***Você pode me ouvir? - Acessando a voz da criança com Autismo e seus pais*** O objetivo deste artigo é acessar as vozes de crianças com Transtorno do Espectro Autista (TEA) e de seus pais. Este artigo aborda estruturas conceituais filosóficas que exploram conceitos de movimento e engajamento como forma de dar voz a crianças e pais. Estudos de caso qualitativos e longitudinais foram conduzidos. Entrevistas semiestruturadas [n = 83] foram realizadas com as partes interessadas, incluindo os pais. Crianças com e sem o diagnóstico de TEA envolveram-se em intervenções baseadas nas Artes Criativas. A autoetnografia viva foi considerada um princípio metodológico, estabelecendo conectividade entre a vida e a pesquisa, o eu e os outros, fornecendo uma janela através da qual o mundo interno dos pais foi interpretado e compreendido. Esta pesquisa permitiu que crianças e pais explorassem seus mundos e deliberassem sobre as áreas que afetaram suas vidas. O valor potencial do uso das Artes Criativas como meio de envolver as crianças com Autismo é discutido. Implicações relacionadas ao movimento [literal e metafórico] e engajamento são exploradas. Palavras-chave: Engajamento; Crianças com Autismo, Voz da criança; Voz dos pais; Inclusão, Movimento; Imitação; Teatro de Fantoches